The relationships between mindfulness, sport anxiety, pessimistic attributions and flow in competitive cyclists - Scott-Hamilton, J.; Schutte, N. S.; Moyle, G. M.; Brown, R. F. (International Journal of Sport Psychology, 2016)
This research investigated a model connecting greater mindfulness to more occurrences of flow and less sport-specific anxiety and pessimistic sport attributions in competitive cyclists. The research examined direct and indirect paths from mindfulness to the subjective state of being in flow. Indirect paths examined were through pessimistic sports attributions, sport-specific anxiety and flow conditions. Key findings were that higher levels of mindfulness were associated with more experience of flow, fewer sports-related pessimistic cognitions, and less sport-specific anxiety. Lower levels of sport-specific pessimistic attributions and sport-specific anxiety were associated with a higher frequency of experienced flow conditions. A higher frequency of flow conditions was associated with more occurrence of the subjective state of being in flow. The results support a model connecting mindfulness to flow experience through the meeting of flow conditions and through less experience of pessimism and anxiety. The results have implications for possible interventions focused upon increasing mindfulness to enhance the occurrence of flow.